2023
DOI: 10.1002/nur.22347
|View full text |Cite
|
Sign up to set email alerts
|

A phenomenological exploration of the mental health experiences of young women with diminished ovarian reserve

Brittany M. Woods,
Leigh Ann Bray,
Sukhkamal B. Campbell
et al.

Abstract: Infertility is a reproductive disease affecting one in six individuals that renders an individual unable to conceive. One cause of infertility is diminished ovarian reserve (DOR), which reduces the quantity and/or quality of a female's oocyte pool. Although typically indicating normal ovarian aging during the late 30s and early 40s, DOR can also impact younger women, increasing their risk for psychological distress from an unexpected diagnosis of infertility. A phenomenological approach examined the mental hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Both studies used qualitative methodologies to examine the mental health experiences of women in adverse situations. Woods and colleagues employed a phenomenological approach to identify the mental health experiences of women with infertility due to diminished ovarian reserve (Woods et al, 2023). The authors found that the women reported feelings of invisibility, hopelessness, and barriers to accessing mental health resources (Woods et al, 2023).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Both studies used qualitative methodologies to examine the mental health experiences of women in adverse situations. Woods and colleagues employed a phenomenological approach to identify the mental health experiences of women with infertility due to diminished ovarian reserve (Woods et al, 2023). The authors found that the women reported feelings of invisibility, hopelessness, and barriers to accessing mental health resources (Woods et al, 2023).…”
mentioning
confidence: 99%
“…Woods and colleagues employed a phenomenological approach to identify the mental health experiences of women with infertility due to diminished ovarian reserve (Woods et al, 2023). The authors found that the women reported feelings of invisibility, hopelessness, and barriers to accessing mental health resources (Woods et al, 2023). They emphasized the need to incorporate mental health screenings and resources into fertility healthcare settings, as well as increasing knowledge and education to facilitate shared decision-making (Woods et al, 2023).…”
mentioning
confidence: 99%
See 1 more Smart Citation